Photovoltaic module frame material and preparation method thereof, and photovoltaic module
Patent Information
- Application Number
- CN202611076404.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,目前用于太阳能光伏组件框架的材料主要是铝合金材料,铝合金材料制成的太阳能光伏组件框架在沿海高盐雾环境(盐雾浓度≥3mg/m3)下易发生电化学腐蚀,导致边框氧化、开裂,缩短组件寿命
[0043]本申请实施例提供的光伏组件边框材料及其制备方法、光伏组件边框,通过设置包括环氧树脂和玻璃纤维无捻粗纱的基体层、包括玻璃纤维缝编织物和改性聚氨酯树脂的中间层以及包括玄武岩纤维毡和耐候聚氨酯树脂的防护层,能够使光伏组件边框在保证主体承载强度的同时提高横向支撑能力、层间结合性能和外部环境防护能力,进而提升边框在高盐雾、湿热及温差循环环境中的耐腐蚀性、耐候稳定性及长期服役可靠性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic modules, and in particular to a photovoltaic module frame material and its preparation method, and a photovoltaic module. Background Technology
[0002] As a core structural component of photovoltaic modules, the frame material is widely used in large-scale ground-mounted photovoltaic power plants, distributed rooftop photovoltaic systems, photovoltaic projects in deserts / saline-alkali lands, and photovoltaic installations in coastal areas with high salt spray and high humidity. In harsh outdoor environments, the frame must withstand long-term wind and sand erosion, salt spray corrosion, ultraviolet radiation, diurnal temperature variation (such as diurnal temperature variation exceeding 40°C in desert areas), and mechanical loads (such as wind pressure and hail impact).
[0003] However, the main material currently used for solar photovoltaic module frames is aluminum alloy. Solar photovoltaic module frames made of aluminum alloy are susceptible to damage in coastal high-salt-fog environments (salt spray concentration ≥3 mg / m³). 3 Electrochemical corrosion easily occurs under certain conditions, leading to frame oxidation and cracking, thus shortening the module's lifespan. To improve the electrochemical corrosion problem of solar photovoltaic module frames, researchers have also proposed a photovoltaic module frame material based on glass fiber reinforced unsaturated polyester resin. This material has good insulation properties and is less prone to electrochemical corrosion, but its weather resistance is poor, making it susceptible to pulverization and embrittlement. Furthermore, its insufficient bending strength cannot meet the mechanical strength requirements of photovoltaic modules to withstand wind pressure and hail impacts in harsh outdoor environments.
[0004] Therefore, there is an urgent need to develop a photovoltaic module frame material that is lightweight, high-strength, and weather-resistant to meet the reliability and economic requirements in complex environments. Summary of the Invention
[0005] This application provides a photovoltaic module frame material and its preparation method, as well as a photovoltaic module frame, to improve the comprehensive mechanical properties, weather resistance, and reliability of the photovoltaic module frame under conditions such as salt spray, damp heat, and temperature difference cycling.
[0006] In a first aspect, embodiments of this application provide a photovoltaic module frame material, including a substrate layer, an intermediate layer, and a protective layer;
[0007] The matrix layer comprises epoxy resin and glass fiber roving;
[0008] The intermediate layer comprises a glass fiber woven fabric and a modified polyurethane resin;
[0009] The protective layer comprises basalt fiber felt and weather-resistant polyurethane resin.
[0010] In one possible implementation, the linear density of the glass fiber roving is 1200 tex-4800 tex;
[0011] And / or, the epoxy resin includes bisphenol F type epoxy resin;
[0012] And / or, the density of the glass fiber stitched fabric is 300 g / m³. 2 -650g / m 2 ;
[0013] And / or, the modified polyurethane resin includes at least one of polyether-modified polyurethane, polyester-modified polyurethane, epoxy-modified polyurethane, amino-terminated polyether-modified polyurethane, and silicone-modified polyurethane.
[0014] And / or, the density of the basalt fiber felt is 30 g / m³. 2 -100g / m 2 ;
[0015] And / or, the weather-resistant polyurethane resin includes aliphatic isocyanate-modified polyurethane.
[0016] In one possible implementation, the glass fiber stitched fabric comprises a biaxial glass fiber stitched fabric;
[0017] And / or, the aliphatic isocyanate modified polyurethane resin includes at least one of hexamethylene diisocyanate modified polyurethane, isophorone diisocyanate modified polyurethane, dicyclohexylmethane diisocyanate modified polyurethane, and tetramethylxylene diisocyanate modified polyurethane.
[0018] In one possible implementation, the matrix layer comprises, by weight percentage: 30%-40% epoxy resin, 50%-65% glass fiber roving, 1%-2% silane coupling agent, 2%-5% toughening agent, and 1%-3% curing agent;
[0019] And / or, the intermediate layer comprises: 60%-75% of the glass fiber stitched fabric and 25%-40% of the modified polyurethane resin;
[0020] And / or, the protective layer comprises: 45%-55% of the basalt fiber felt, 40%-50% of the weather-resistant polyurethane resin, 0.5%-1.5% of the ultraviolet absorber, 0.3%-1% of the light stabilizer, and 0.2%-0.8% of the antioxidant.
[0021] In one possible implementation, the silane coupling agent includes at least one of aminosilane coupling agents, epoxysilane coupling agents, and mercaptosilane coupling agents.
[0022] And / or, the toughening agent includes at least one of liquid nitrile rubber, carboxyl-terminated nitrile rubber, core-shell acrylate, and polyether polyurethane;
[0023] And / or, the curing agent includes at least one of aliphatic polyamines, modified aromatic amines, cycloaliphatic amines, and phenolic amine curing agents;
[0024] And / or, the ultraviolet absorber includes at least one of benzotriazole, triazine, and benzophenone ultraviolet absorbers;
[0025] And / or, the light stabilizer includes hindered amine compounds;
[0026] And / or, the antioxidant includes at least one of phenolic antioxidants, phosphite antioxidants, and thioether antioxidants.
[0027] In one possible implementation, the photovoltaic module frame material comprises, by weight percentage, 40%-55% of the substrate layer, 30%-40% of the intermediate layer, and 10%-15% of the protective layer.
[0028] Secondly, embodiments of this application provide a method for preparing the photovoltaic module frame material, comprising: preparing a matrix layer resin slurry, an intermediate layer resin slurry, and a protective layer resin slurry respectively, and then impregnating the glass fiber roving, the glass fiber stitched fabric, and the basalt fiber felt into the corresponding matrix layer resin slurry, the intermediate layer resin slurry, and the protective layer resin slurry;
[0029] The three types of impregnated fibers are simultaneously subjected to impregnation, curing, and heat preservation treatments in sequence, followed by pultrusion treatment to obtain the photovoltaic module frame material.
[0030] In one possible implementation, the matrix resin slurry includes a silane coupling agent, a toughening agent, a curing agent, and the epoxy resin;
[0031] And / or, the intermediate layer resin slurry includes the modified polyurethane resin;
[0032] And / or, the protective layer resin slurry includes an ultraviolet absorber, a light stabilizer, an antioxidant, and the weather-resistant polyurethane resin.
[0033] In one possible implementation, the volume-to-mass ratio of the matrix resin slurry to the glass fiber roving is (0.35-0.55) mL:1g;
[0034] And / or, the volume-to-mass ratio of the intermediate layer resin slurry to the glass fiber stitched fabric is (0.28-0.42) mL: 1 g;
[0035] And / or, the volume-to-mass ratio of the protective layer resin slurry to the basalt fiber felt is (0.40-0.60) mL:1g.
[0036] In one possible implementation, the immersion temperature is 40°C-60°C, and the immersion time is 10 min-15 min;
[0037] And / or, the temperature of the immersion treatment is 80℃-120℃;
[0038] And / or, the curing temperature is 180℃-230℃;
[0039] And / or, the temperature of the heat preservation treatment is 140℃-180℃;
[0040] And / or, the pultrusion process is performed at a speed of 1.2 m / min to 1.6 m / min.
[0041] Thirdly, embodiments of this application provide a photovoltaic module frame, including the photovoltaic module frame material described above or the photovoltaic module frame material prepared by the preparation method described above.
[0042] Fourthly, embodiments of this application provide a photovoltaic module, the photovoltaic module including the aforementioned photovoltaic module frame.
[0043] The photovoltaic module frame material and its preparation method provided in this application, and the photovoltaic module frame, by setting a matrix layer including epoxy resin and glass fiber untwisted roving, an intermediate layer including glass fiber woven fabric and modified polyurethane resin, and a protective layer including basalt fiber felt and weather-resistant polyurethane resin, can improve the lateral support capacity, interlayer bonding performance and external environmental protection capacity of the photovoltaic module frame while ensuring the main load-bearing strength. In this way, the corrosion resistance, weathering stability and long-term service reliability of the frame are improved in high salt spray, humid heat and temperature difference cycling environments. Detailed Implementation
[0044] Exemplary embodiments will be described in detail below. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.
[0045] Current photovoltaic module frames primarily utilize aluminum alloy profiles or fiber-reinforced composite profiles, formed through extrusion or pultrusion molding, respectively, to achieve the required cross-sectional structure. Aluminum alloy frames rely on continuous extrusion processes of metal profiles to achieve relatively stable dimensional accuracy and mature assembly methods. Their working mechanism lies in utilizing the high overall stiffness of the metal material to bear the load on the outer edge of the module, and achieving edge locking, embedding, and installation connection functions through profile cross-section design. Fiber-reinforced composite frames typically use resin as the matrix and glass fiber or other reinforcing materials as the skeleton. The fibers are impregnated with resin and then cured during pultrusion. The fibers bear the main load, while the resin transfers stress and protects the fibers, achieving weight reduction and insulation. However, both of these technical approaches have revealed significant shortcomings in complex outdoor environments. Aluminum alloy frames are prone to corrosion in high salt spray and humid environments. Corrosion not only affects appearance but also weakens local strength and connection reliability. Furthermore, aluminum alloys and photovoltaic glass exhibit significant differences in thermal expansion behavior. Under conditions of large diurnal temperature variations, strong seasonal temperature differences, or rapid thermal cycling, interfacial thermal stress can easily form between the frame and glass. Long-term accumulation of this stress can lead to stress concentration at glass edges, fatigue in the sealing area, and even microcracks in the module. For large-size modules, as the frame span increases, traditional metal frames, while possessing a certain degree of rigidity, exhibit increasingly prominent shortcomings in weight, corrosion sensitivity, and thermal matching. While composite material frames offer lightweight advantages, existing solutions often employ relatively simple fiber-reinforced resin structures. Their stress characteristics are often better in the main fiber direction, but insufficient in lateral, corner, or complex load conditions. This makes the frames more susceptible to localized cracking, delamination, or permanent deformation under wind pressure, snow loads, or impact loads. Meanwhile, composite materials may experience resin aging, interface degradation, and surface performance deterioration under long-term ultraviolet radiation, humid heat corrosion, and salt spray environments. If the resin does not wet the fibers evenly during the molding process, it can also form pores, dry spots, or weak interfacial areas, further weakening the overall strength of the frame and its compatibility with the component encapsulation boundary. In other words, existing frame technologies either have deficiencies in corrosion resistance and thermal matching, or are insufficient in lateral load-bearing capacity, weather resistance stability, and molding consistency, making it difficult to simultaneously meet the comprehensive requirements of high strength, lightweight, long-term durability, and structural stability in complex application scenarios.
[0046] The photovoltaic module frame material provided in this application includes a substrate layer, an intermediate layer, and a protective layer. The substrate layer comprises epoxy resin and untwisted glass fiber roving, the intermediate layer comprises woven glass fiber fabric and modified polyurethane resin, and the protective layer comprises basalt fiber felt and weather-resistant polyurethane resin. This layered frame structure provides foundation support, reinforces load-bearing capacity, and protects against external environmental factors, ensuring the frame maintains necessary structural strength during long-term module operation while exhibiting good stability under conditions such as salt spray, humidity, ultraviolet radiation, and temperature cycling. Considering the structural scenario where the photovoltaic module frame surrounds the laminated component and works in conjunction with an installation system, this frame can be directly used as the outer frame of the module in large-scale ground-mounted power plants, coastal areas, desert areas, plateau areas, and distributed rooftop systems. The synergistic configuration of the substrate layer, intermediate layer, and protective layer overcomes the difficulty of traditional single-material frames in simultaneously achieving strength, durability, and adaptability, providing a clear technical foundation for further development of frame structures and their implementation methods. The following detailed embodiments illustrate the technical solution of this application and how it solves the aforementioned technical problems. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments. The embodiments of this application will be described below.
[0047] This application provides a photovoltaic module frame material, including a substrate layer, an intermediate layer, and a protective layer; the substrate layer includes epoxy resin and glass fiber roving; the intermediate layer includes glass fiber woven fabric and modified polyurethane resin; the protective layer includes basalt fiber felt and weather-resistant polyurethane resin.
[0048] In this embodiment, the photovoltaic module frame is used to surround the photovoltaic module laminate, forming an outer frame structure that combines load-bearing, edge sealing protection, and environmental isolation functions. To ensure the frame maintains structural stability under long-term outdoor wind pressure, snow load, humidity and heat, salt spray, ultraviolet radiation, and thermal cycling conditions, this embodiment designs the frame as a three-layer composite structure with functional layering features. The base layer serves as the main load-bearing skeleton, the middle layer serves as a horizontal and vertical synergistic reinforcement layer, and the protective layer serves as a barrier layer against the external environment. The three layers are sequentially composited in the thickness direction and can extend continuously along the circumference of the frame profile, thereby forming a continuous and stable composite force-bearing system in the length direction, cross-sectional direction, and environmentally exposed surface direction. Based on the above structural configuration, the base layer takes priority in bearing the basic tensile, bending and compressive loads of the outer edge of the component. The intermediate layer reinforces the main load-bearing layer in-plane and out-of-plane and improves the stress dispersion ability under complex loads. The protective layer shields against rainwater, salt spray, ultraviolet rays and oxidizing media, thereby reducing the intrusion rate of external media into the internal resin and fiber interface, so that the frame can be adapted to long-term service scenarios such as large ground power plants, coastal high salt spray areas, desert sandstorm areas and plateau strong ultraviolet areas.
[0049] Specifically, the matrix layer comprises epoxy resin and glass fiber roving.
[0050] In some embodiments, bisphenol F epoxy resin can be selected as the epoxy resin, and it is combined with an amino curing agent, a silane coupling agent, and a rubber toughening agent to form a resin system that balances wettability, curing activity, and toughness. Bisphenol F epoxy resin has lower viscosity and better fiber wetting ability compared to conventional systems, making it easier to penetrate the glass fiber bundle during continuous molding, reducing dry spots and localized resin-deficient areas. The amino curing agent promotes the cross-linking reaction of epoxy groups, enabling the cured matrix to form a dense three-dimensional network structure, improving thermal stability and mechanical retention. The silane coupling agent can build a chemical bridge between the inorganic glass fiber surface and the organic resin interface, improving interfacial shear strength and allowing the load to be transferred more effectively from the resin to the fiber. The rubber toughening agent improves the crack propagation resistance of the cured material under impact and cyclic stress conditions by introducing a toughening phase into the cross-linked network.
[0051] In some specific implementations, the glass fiber roving is preferably alkali-free glass fiber roving with a linear density controlled between 1200 tex and 4800 tex. This is beneficial for balancing the load-bearing capacity of the monofilament bundle and the resin impregnation depth during continuous pultrusion molding. When the linear density is too low, although impregnation is easy, the fiber skeleton per unit cross-section is insufficient, limiting the improvement in the longitudinal stiffness of the frame. When the linear density is too high, the fiber bundle is not easily fully impregnated, easily forming residual pores and weak interfacial areas. Therefore, by selecting appropriate specifications within this range, the matrix layer can form a continuous, directional, and high-volume-fraction main load-bearing path, thereby providing the frame with the main longitudinal bending and tensile support capabilities.
[0052] For example, the linear density of the glass fiber untwisted coarse grit can be a range of 1200tex, 1400tex, 1600tex, 1800tex, 2000tex, 2400tex, 2800tex, 3200tex, 3600tex, 4000tex, 4400tex, 4800tex or any combination thereof.
[0053] In some specific embodiments, the matrix layer comprises, by weight percentage: 30%-40% epoxy resin, 50%-65% glass fiber roving, 1%-2% silane coupling agent, 2%-5% toughening agent, and 1%-3% curing agent.
[0054] The matrix layer uses epoxy resin as the continuous phase and glass fiber roving as the main load-bearing skeleton. Silane coupling agent is used in the matrix layer to form a chemical bridge between the glass fiber and epoxy resin, improving wettability and load transfer efficiency, thereby inhibiting interfacial debonding. Toughening agent is used to improve the brittleness of the epoxy system, absorbing impact energy and blunting crack tips through the elastic phase, making the frame less prone to cracking under wind load, hoisting and installation impact. Curing agent is used to adjust the crosslinking rate and crosslinking density of epoxy resin, so that the curing process takes into account both the process window and the final strength, thereby improving molding stability.
[0055] By controlling the mass fraction of epoxy resin to 30%-40%, the mass fraction of glass fiber roving to 50%-65%, and combining it with 1%-2% silane coupling agent, 2%-5% toughening agent, and 1%-3% curing agent, a stable chemical bond can be formed between the resin and the glass fiber roving. This allows the resin to more fully wet the fiber and form a stable cross-linked network. The silane coupling agent establishes a chemical bridge between the fiber surface and the resin, the toughening agent absorbs impact and alleviates brittleness, and the curing agent controls the curing rate and cross-linking density, thereby improving interfacial bonding strength, dimensional stability, and crack resistance.
[0056] For example, by weight percentage, the matrix layer comprises 30% epoxy resin, 65% glass fiber roving, 1% silane coupling agent, 2% toughening agent, and 2% curing agent; or, the matrix layer comprises 35% epoxy resin, 60% glass fiber roving, 2% silane coupling agent, 2% toughening agent, and 1% curing agent; or, the matrix layer comprises 40% epoxy resin, 50% glass fiber roving, 2% silane coupling agent, 5% toughening agent, and 3% curing agent.
[0057] In some specific embodiments, the silane coupling agent includes at least one of aminosilane coupling agents, epoxysilane coupling agents, and mercaptosilane coupling agents.
[0058] In some specific embodiments, the toughening agent includes at least one of liquid nitrile rubber, carboxyl-terminated nitrile rubber, core-shell acrylate, and polyether polyurethane.
[0059] In some specific embodiments, the curing agent includes at least one of aliphatic polyamines, aromatic amines, cycloaliphatic amines, and phenolic amines.
[0060] The toughening agent can preferably be an elastomer or core-shell type component to improve the impact and crack resistance of the cured layer; the curing agent can be an amine or anhydride curing agent according to the epoxy system to match the gel speed and demolding strength required for pultrusion molding.
[0061] The intermediate layer consists of fiberglass woven fabric and modified polyurethane resin.
[0062] In some embodiments, the fiberglass stitched fabric can employ a 0° / 90° bidirectional stitched structure, which establishes a bidirectional load-dispersing network in the frame cross-section and circumferential direction through the orderly arrangement of warp and weft fibers. Compared to unidirectional continuous fiber structures, bidirectional stitched fabrics can more effectively disperse lateral and tangential stresses when subjected to bending and torsional coupling loads caused by wind pressure, local compressive stresses caused by installation clamping, and complex stresses in corner connection areas, reducing the risk of cracking and delamination in the lateral and corner areas of traditional composite frame materials. The biaxial structure also facilitates resin impregnation and maintains a more stable pore distribution, thereby improving the quality of interlayer bonding.
[0063] In some specific embodiments, the areal density of the fiberglass stitched fabric is 300 g / m². 2 -650g / m 2 .
[0064] By adjusting the density of the fiberglass stitched fabric within this range, a balance can be achieved between reinforcement and impregnation moldability, for example, 450 g / m². 2 Up to 500g / m 2 It is more suitable for balancing lateral bending resistance and processing fluidity.
[0065] For example, the areal density of the fiberglass sewn fabric can be 300 g / m². 2 350g / m 2 400g / m 2 450g / m 2 500g / m 2 550g / m 2 600g / m 2 650g / m 2 Or a range consisting of any two of them.
[0066] In some specific embodiments, the modified polyurethane resin includes at least one of polyether-modified polyurethane, polyester-modified polyurethane, epoxy-modified polyurethane, amino-terminated polyether-modified polyurethane, and silicone-modified polyurethane.
[0067] Its function is to improve the toughness, moisture and heat resistance and stress buffering capacity of the intermediate layer, so as to form a more reliable transition reinforcement zone between the stitched fabric and the upper and lower layers.
[0068] In some specific embodiments, the intermediate layer comprises, by weight percentage: 60%-75% glass fiber woven fabric and 25%-40% modified polyurethane resin.
[0069] In this embodiment, the mass percentage of glass fiber woven fabric and modified polyurethane resin contained in the intermediate layer is controlled within the above range to balance strength and molding density.
[0070] By controlling the ratio, the intermediate layer can maintain a high fiber skeleton ratio for effective reinforcement, while ensuring sufficient resin content to fully cover the bidirectional fabric nodes, interlacing areas, and interlayer interfaces, thus forming a relatively strong composite interface between the intermediate layer and the matrix layer. The impregnation temperature of the intermediate layer can be matched with that of the matrix layer to avoid the problem of asynchronous impregnation caused by excessive viscosity differences between different layer materials in the pre-molding stage.
[0071] In another possible embodiment, the intermediate layer can employ a gradient density design, with a higher-density woven fabric on the side closer to the matrix layer and a lower-density woven fabric on the side farther from the matrix layer. This gradient distribution allows the intermediate layer to provide stronger structural constraints and load-bearing capacity closer to the main load-bearing layer, while reducing abrupt changes in local stiffness on the side closer to the protective layer. This is beneficial for optimizing interlayer thermal expansion matching and reducing residual stress at the interface.
[0072] For example, by weight percentage, the intermediate layer comprises 60% glass fiber woven fabric and 40% modified polyurethane resin; or, the intermediate layer comprises 65% glass fiber woven fabric and 35% modified polyurethane resin; or, the intermediate layer comprises 70% glass fiber woven fabric and 30% modified polyurethane resin; or, the intermediate layer comprises 75% glass fiber woven fabric and 25% modified polyurethane resin, and other unlisted cases within the above weight percentage range.
[0073] This intermediate layer provides bidirectional skeletal support through a biaxial fiberglass stitch-woven fabric, and achieves full impregnation, bonding, and stress transfer with modified polyurethane resin. The reaction mechanism involves the formation of a continuous phase after resin curing, firmly locking the fiber bundles and stitches into a unified whole. Because the biaxial fabric improves the load-bearing capacity of the frame in non-primary directions, and the modified polyurethane reduces the impact of environmental aging on interfacial strength, this layer maintains dimensional stability and structural integrity under complex loads and long-term outdoor exposure.
[0074] Through the above structural combination, the intermediate layer can improve the frame's bending, tensile and impact resistance in both longitudinal and transverse directions, and enhance the weather resistance and interface retention of the resin system, thereby reducing performance degradation caused by temperature difference cycling, damp heat erosion and ultraviolet radiation, and thus ensuring the load-bearing reliability and overall stability of the photovoltaic module frame during long-term service.
[0075] The protective layer consists of basalt fiber felt and weather-resistant polyurethane resin.
[0076] In some specific embodiments, the areal density of basalt fiber felt is 30 g / m². 2 -100g / m 2 .
[0077] Basalt fiber, derived from the melting and drawing of natural minerals, possesses excellent high-temperature resistance, corrosion resistance, and UV stability. When fabricated into a felt-like structure, it forms a uniform and continuous protective skeleton on the outermost layer, allowing the surface resin to maintain structural continuity even under external erosion. Lower areal density of the basalt fiber felt reduces resin absorption and maintains lightweight properties, while higher areal density facilitates the formation of a more complete surface protective skeleton, thereby enhancing resistance to UV radiation, salt spray, and abrasive environments. Therefore, an areal density of 30 g / m² was chosen. 2 -100g / m 2 Basalt fiber felt is beneficial for balancing the thickness of the intermediate layer, the difficulty of resin coating, and the erosion resistance of the intermediate layer.
[0078] For example, the areal density of basalt fiber felt can be 30 g / m³. 2 40g / m 2 50g / m 2 60g / m 2 70g / m 2 80g / m 2 90g / m 2 100g / m 2 Or a range consisting of any two of them.
[0079] In some specific embodiments, the weather-resistant polyurethane resin includes aliphatic isocyanate-modified polyurethane.
[0080] In some embodiments, the aliphatic isocyanate-modified polyurethane includes at least one of hexamethylene diisocyanate-modified polyurethane, isophorone diisocyanate-modified polyurethane, dicyclohexylmethane diisocyanate-modified polyurethane, and tetramethylxylene diisocyanate-modified polyurethane.
[0081] For aliphatic isocyanate-modified polyurethane resins, hexamethylene diisocyanate-modified polyurethane is preferred. Its aliphatic structure reduces sensitivity to photothermal aging and enhances stability under humid, hot, and UV conditions. After curing, this type of resin forms a flexible and well-adhesive network, which better encapsulates glass fibers and buffers interfacial stress caused by thermal expansion and contraction, thereby inhibiting cracking and delamination. Using hexamethylene diisocyanate-modified polyurethane and similar aliphatic modified resins within the same system can balance impregnation flowability with post-curing weather resistance retention, ensuring the protective layer maintains stable reinforcement under long-term outdoor conditions.
[0082] After the weather-resistant polyurethane resin is modified with aliphatic isocyanate, the anti-yellowing and weather resistance retention rate of the outer layer can be significantly improved. The reaction mechanism is that the aliphatic structure is more stable to ultraviolet aging, and when combined with basalt fiber felt, it can form a dense and durable protective interface.
[0083] In the protective layer, weather-resistant polyurethane resin can be combined with ultraviolet absorbers, light stabilizers, and antioxidants to form a weather-resistant protective combination, which improves outdoor durability through a synergistic anti-aging principle. Ultraviolet absorbers absorb high-energy ultraviolet light and convert it into low-hazard heat energy, slowing down resin chain breakage; light stabilizers capture free radicals and inhibit photo-oxidation chain reactions, delaying surface chalking and embrittlement; antioxidants preferentially consume active free radicals generated under thermo-oxidative environments, reducing the degradation rate caused by high temperature, thermal cycling, and oxygen diffusion. By synergistically configuring the above additives with basalt fiber felt and weather-resistant polyurethane resin, the frame can maintain stable interlayer bonding, high surface weather resistance, and slower long-term mechanical property degradation in salt spray, humid heat, and strong ultraviolet environments, thereby improving the service life and structural reliability of photovoltaic module frames.
[0084] In some specific embodiments, the protective layer comprises, by weight percentage: 45%-55% basalt fiber felt, 40%-50% weather-resistant polyurethane resin, 0.5%-1.5% ultraviolet absorber, 0.3%-1% light stabilizer, and 0.2%-0.8% antioxidant.
[0085] By controlling the content of each component in the protective layer within the above-mentioned range, the resistance of the protective layer to ultraviolet aging, salt spray corrosion and humid heat oxidation can be improved without excessively affecting the resin curing and mechanical properties.
[0086] For example, by weight percentage, the protective layer may include 47% basalt fiber felt, 50% weather-resistant polyurethane resin, 1.5% ultraviolet absorber, 1% light stabilizer, and 0.5% antioxidant; or, the protective layer may include 50% basalt fiber felt, 48% weather-resistant polyurethane resin, 1% ultraviolet absorber, 0.5% light stabilizer, and 0.5% antioxidant; or, the protective layer may include 55% basalt fiber felt, 44% weather-resistant polyurethane resin, 0.5% ultraviolet absorber, 0.3% light stabilizer, and 0.2% antioxidant, and other unlisted cases within the above weight percentage range.
[0087] In another possible embodiment, the protective layer can be made of multi-directional stitched basalt fiber cloth instead of basalt fiber felt to enhance the isotropic mechanical properties of the outer layer under multi-directional stress, so that in addition to the weather-resistant barrier function, the outer layer can also provide better dispersion of transient loads such as hail impact and transportation collision.
[0088] In another possible embodiment, the weather-resistant polyurethane resin may also incorporate nano-silica or nano-zinc oxide fillers. Nano-silica improves the resin's density and surface abrasion resistance, while nano-zinc oxide, in addition to enhancing density, also strengthens its ability to scatter and absorb ultraviolet light. Through the combined effect of the nanofillers and the weather-resistant polyurethane, the rate of diffusion of ultraviolet light and corrosive media into the inner layer can be further reduced, thereby delaying long-term erosion of the interface between the intermediate layer and the substrate layer.
[0089] In some specific embodiments, the ultraviolet absorber includes at least one of benzotriazole ultraviolet absorbers, triazine ultraviolet absorbers, and benzophenone ultraviolet absorbers.
[0090] In some specific implementations, the light stabilizer includes hindered amine compounds.
[0091] In some specific embodiments, the antioxidant includes at least one of phenolic antioxidants, phosphite antioxidants, and thioether antioxidants.
[0092] In some specific implementations, the photovoltaic module frame material comprises, by weight percentage, 40%-55% of a substrate layer, 30%-40% of an intermediate layer, and 10%-15% of a protective layer.
[0093] In this embodiment, the mass ratio is used to define the mass percentage of each layer in the overall structure, ensuring that the substrate layer provides the main skeletal support, the intermediate layer provides the main reinforcement, and the protective layer forms the outer surface protection. By controlling the substrate layer to 40%-55% of the photovoltaic module frame material, preferably 50%-55%, it is possible to ensure that the epoxy resin and glass fiber roving form a continuous and dense load-bearing substrate, enhancing the overall stiffness and dimensional stability of the profile. When the intermediate layer is controlled to 30%-40% of the photovoltaic module frame material, preferably 32%-38%, the glass fiber woven fabric and modified polyurethane resin can fully exert their multi-directional reinforcement and stress transfer functions. When the protective layer is controlled to 10%-15% of the photovoltaic module frame material, preferably 10%-12% by weight, the basalt fiber felt and weather-resistant polyurethane resin can form an ultraviolet-resistant and salt spray-resistant outer protective layer without significantly increasing the weight. This weight distribution prioritizes load-bearing capacity in the inner layer, reinforcement in the middle layer, and protection in the outer layer. This avoids both excessively thick protective layers leading to embrittlement and stress accumulation, and insufficient support due to an excessively thin substrate layer, or reduced lateral load-bearing capacity due to an excessively thin middle layer. This process achieves synergistic curing and stress balancing of the three layers during pultrusion or lamination, thereby improving the long-term reliability of the frame under wind pressure, snow load, temperature cycling, and humid salt spray environments. It also ensures stable edge encapsulation and secure installation connections, ultimately guaranteeing the structural integrity and weather resistance of the photovoltaic module during outdoor service.
[0094] For example, by weight percentage, the photovoltaic module frame material comprises a substrate layer of 45%, an intermediate layer of 40%, and a protective layer of 15%; or, the photovoltaic module frame material comprises a substrate layer of 50%, an intermediate layer of 40%, and a protective layer of 10%; or, the photovoltaic module frame material comprises a substrate layer of 55%, an intermediate layer of 35%, and a protective layer of 10%; or, the photovoltaic module frame material comprises a substrate layer of 55%, an intermediate layer of 30%, and a protective layer of 15%, and other unlisted cases within the above weight percentage range.
[0095] The photovoltaic module frame material provided in this application includes a substrate layer, an intermediate layer, and a protective layer. The substrate layer includes epoxy resin and untwisted glass fiber roving; the intermediate layer includes glass fiber woven fabric and modified polyurethane resin; and the protective layer includes basalt fiber felt and weather-resistant polyurethane resin. In this embodiment, by constructing the frame as a three-layer composite structure with a high-strength load-bearing inner layer, bidirectional reinforcement in the middle layer, and weather-resistant protection on the outer layer, and combining it with a suitable resin system, fiber specifications, proportion range, and continuous pultrusion molding process, it can simultaneously ensure mechanical support capacity, weather resistance stability, thermal deformation adaptability, and long-term structural reliability in complex outdoor service environments. This allows the frame to better meet the long-term use requirements of large-scale ground power plants, coastal areas, desert areas, plateau areas, and distributed rooftop systems.
[0096] Compared to single aluminum alloy frames, the photovoltaic module frame material provided in this application can reduce salt spray corrosion sensitivity and improve thermal compatibility with components such as glass. Compared to traditional single fiber-reinforced composite material frames, it can improve lateral load-bearing capacity, interlayer bonding, and long-term weather resistance. Especially in large-size, high-power photovoltaic module applications, the combination of the continuous longitudinal stiffness provided by the substrate layer and the bidirectional reinforcement provided by the intermediate layer can effectively suppress the deflection and local deformation of the frame under large span conditions. Meanwhile, the protective layer's barrier effect against damp heat, ultraviolet rays, and salt spray can delay resin aging and interface degradation, thereby ensuring that the module maintains high structural reliability and encapsulation boundary stability during transportation, hoisting, installation, and long-term power generation operation.
[0097] This application embodiment also provides a method for preparing the above-mentioned photovoltaic module frame material, the method comprising:
[0098] The matrix layer resin slurry, intermediate layer resin slurry and protective layer resin slurry are prepared separately, and then glass fiber roving, glass fiber stitched fabric and basalt fiber mat are impregnated into the corresponding matrix layer resin slurry, intermediate layer resin slurry and protective layer resin slurry.
[0099] The three types of impregnated fibers were simultaneously subjected to impregnation, curing, and heat insulation treatments, followed by pultrusion to obtain the photovoltaic module frame material.
[0100] The frame of a photovoltaic module can be integrally manufactured using a three-layer gradient composite structure through pultrusion molding. For example, the manufacturing process may include fiber drying, separate impregnation of the three layers, three-zone temperature-controlled pultrusion molding, and post-processing cutting and chamfering.
[0101] Specifically, the glass fiber roving, glass fiber woven fabric, and basalt fiber felt are first pretreated, with continuous fibers and fabric materials having their adsorbed moisture removed by a drying device. Then, they are impregnated in corresponding resin tanks, so that the matrix layer resin slurry, intermediate layer resin slurry, and protective layer resin slurry coat the corresponding reinforcing materials according to a predetermined ratio. Then, the three layers of materials are composited and assembled according to a preset cross-sectional shape through a yarn guide mold, a preforming mold, and a heating mold, and continuously passed through a temperature-controlled area under pultrusion traction to complete the curing and molding process.
[0102] In some embodiments, the matrix layer resin slurry includes a silane coupling agent, a toughening agent, a curing agent, and an epoxy resin.
[0103] For the matrix layer resin slurry, the epoxy resin can be heated to a fluid state first, and then a silane coupling agent can be added and dispersed at a low speed to improve the uniformity of the coupling agent in the resin. Then, a toughening agent is added and stirring is continued to form a continuous dispersed phase in the epoxy system. Finally, a curing agent is added before use and an appropriate working time is controlled to avoid premature gelation.
[0104] In some embodiments, the intermediate layer resin slurry comprises a modified polyurethane resin.
[0105] The intermediate layer resin slurry can be made directly from modified polyurethane resin. If necessary, the viscosity can be controlled to make it suitable for impregnation and coating of glass fiber woven fabric, thereby improving interlayer flexibility and load transfer adaptability.
[0106] In some embodiments, the protective layer resin slurry includes an ultraviolet absorber, a light stabilizer, an antioxidant, and a weather-resistant polyurethane resin.
[0107] The protective layer resin slurry can be made by sequentially adding ultraviolet absorbers, light stabilizers and antioxidants to weather-resistant polyurethane resin and then homogenizing and dispersing them so that the additives form a synergistic protective system in the outer layer. The ultraviolet absorbers are used to weaken the incident ultraviolet energy, the light stabilizers are used to inhibit the photodegradation of polymer chains, the antioxidants are used to delay thermo-oxidative aging, and the weather-resistant polyurethane resin serves as a continuous phase to provide outer coating and environmental isolation.
[0108] By separately preparing and impregnating the matrix layer resin slurry, intermediate layer resin slurry, and protective layer resin slurry with their respective fibers, and then simultaneously performing impregnation, curing, and heat preservation treatments under pultrusion, the interfacial bonding and structural shaping of each layer can be completed in the same continuous molding process. The silane coupling agent in the matrix layer resin slurry is preferably controlled to fully cover the fiber surface to enhance the interfacial bonding between the epoxy resin and the glass fiber roving. The addition of a toughening agent can suppress curing brittleness without significantly reducing stiffness. The selection and dosage of the curing agent are used to match the pultrusion line speed and mold temperature to ensure that the matrix layer completes the necessary curing before demolding. When the intermediate layer uses modified polyurethane resin, its flexibility and strain coordination ability can compensate for the performance differences between the matrix layer and the protective layer, reducing the risk of interlayer delamination. The combination of ultraviolet absorbers, light stabilizers, and antioxidants in the protective layer can respectively address photoaging, free radical chain reactions, and thermo-oxidative degradation processes, thereby enabling the outer layer to maintain relatively stable mechanical and appearance properties under long-term outdoor exposure. By applying the aforementioned resin system to the matrix layer, intermediate layer, and protective layer respectively, and forming a layered structure with the corresponding reinforcement, a progressively layered load-bearing, buffering, and protective mechanism can be established within the frame cross-section. This improves the long-term reliability of the photovoltaic module frame under wind pressure, temperature difference, humidity, and ultraviolet environments, and enhances its matching stability with the glass encapsulation boundary. It should be understood that the above example is merely illustrative and not limiting.
[0109] In one possible embodiment, when preparing the three resin slurries separately, epoxy resin, modified polyurethane resin, and weather-resistant polyurethane resin can be added to their respective mixing containers first, followed by the addition of corresponding additives and uniform dispersion to achieve a suitable impregnation viscosity. Then, glass fiber roving, glass fiber woven fabric, and basalt fiber mat are fed into their respective impregnation tanks, ensuring the fibers are fully wetted and air is expelled as they pass through the impregnation zone, thereby reducing porosity and dry spots. After impregnation, the three fibers undergo simultaneous and sequential impregnation, curing, and heat preservation treatments under pultrusion, and are continuously molded using a pultrusion die.
[0110] The impregnation treatment is used to further promote the penetration of resin into the fiber bundle and the gaps in the fabric; the curing treatment is used to achieve preliminary cross-linking and shaping in the mold; the heat preservation treatment is used to cure the resin system after completion and reduce internal stress; and the pultrusion treatment is used to obtain stable cross-section and consistency in the length direction under continuous traction conditions.
[0111] In some specific embodiments, the volume-to-mass ratio of the matrix resin slurry to the glass fiber roving is (0.35-0.55) mL:1g.
[0112] In some specific embodiments, the volume-to-mass ratio of the intermediate layer resin slurry to the glass fiber stitched fabric is (0.28-0.42) mL:1g.
[0113] In some specific embodiments, the volume-to-mass ratio of the protective layer resin slurry to the basalt fiber felt is (0.40-0.60) mL:1g.
[0114] The above volume-to-mass ratio is used to define the ratio between each layer of resin slurry and the corresponding fiber, thereby controlling the impregnation amount, coating degree and residual amount of pores.
[0115] For the matrix layer, the volume-to-mass ratio of the matrix layer resin slurry to the glass fiber roving can be set to ensure that the resin can fully wet the surface of the 1200tex-4800tex roving and fill the gaps between the fiber bundles, while avoiding excessive resin causing embrittlement or insufficient resin causing dry spots. It can be controlled within the range of (0.35-0.55) mL: 1g to ensure that the matrix layer forms a dense and continuous load-bearing skeleton.
[0116] For example, the volume-to-mass ratio of the matrix resin slurry to the glass fiber untwisted coarse sand can be a range of 0.35 ml: 1 g, 0.45 ml: 1 g, 0.55 ml: 1 g, or any combination thereof.
[0117] For the intermediate layer, the volume-to-mass ratio of the intermediate layer resin slurry to the glass fiber stitched fabric can be used to adjust the wetting depth of the modified polyurethane resin in the biaxial stitched fabric, so that the resin can both coat the fiber interlacing nodes and not reduce the interlayer toughness due to resin enrichment. The preferred range is (0.28-0.42) mL:1g, which can make the intermediate layer take into account both lateral crack resistance and impact buffering performance.
[0118] For example, the volume-to-mass ratio of the intermediate layer resin slurry to the glass fiber stitched fabric can be a range of 0.28 ml: 1 g, 0.30 ml: 1 g, 0.32 ml: 1 g, 0.34 ml: 1 g, 0.36 ml: 1 g, 0.38 ml: 1 g, 0.40 ml: 1 g, 0.42 ml: 1 g, or any combination thereof.
[0119] For the protective layer, the volume-to-mass ratio of the protective layer resin slurry to the basalt fiber felt is used to ensure that the weather-resistant polyurethane resin is fully impregnated at 30 g / m². 2 -100g / m 2 Basalt fiber felt is used to form a continuous, weather-resistant, and dense layer on the surface to improve its resistance to ultraviolet rays, damp heat, and salt spray. The preferred ratio is (0.40-0.60) mL:1g to avoid resin buildup or fiber exposure on the protective layer surface.
[0120] For example, the volume-to-mass ratio of the protective layer resin slurry to the basalt fiber felt can be 0.40 ml: 1 g, 0.45 ml: 1 g, 0.50 ml: 1 g, 0.55 ml: 1 g, 0.60 ml: 1 g, or any combination thereof.
[0121] Based on the above analysis, it can be seen that the above volume-to-mass ratio parameter can be set according to the actual process requirements. It should be understood that the above example is only for demonstration and is not a limitation.
[0122] By controlling the volumetric mass ratio of resin slurry to fiber reinforcement in the matrix layer, intermediate layer, and protective layer respectively, a composite structure with a gradual transition from the inside to the outside can be formed during the pultrusion impregnation process. Specifically, the matrix layer is formed by fully impregnating glass fiber roving with an appropriate amount of epoxy resin to form a high-strength main skeleton; the intermediate layer improves interfacial toughness and interlaminar shear resistance by matching the ratio of modified polyurethane resin to glass fiber stitched fabric; and the protective layer is constructed by combining weather-resistant polyurethane resin with basalt fiber felt to create an environmentally resistant outer layer. Since the reinforcement morphology, density, and liquid absorption characteristics of different layers vary, the volumetric mass ratio must be set to balance flowability, impregnation, and curing shrinkage control to ensure that each layer forms a continuous, low-porosity, and mechanically stable composite material during simultaneous impregnation, curing, and insulation. By controlling this volumetric mass ratio within a range suitable for continuous pultrusion molding, the dimensional stability, load-bearing uniformity, and long-term weather resistance of the frame can be effectively improved, thereby meeting the long-term service requirements of photovoltaic modules in complex outdoor environments.
[0123] It should be understood that the above examples are for illustrative purposes only and are not intended to be limiting.
[0124] In some specific embodiments, the immersion temperature when the three fibers are respectively immersed in the corresponding resin slurry is 40℃-60℃, and the immersion time is 10min-15min.
[0125] By controlling the temperature and time during impregnation, the viscosity of the slurry can be reduced and the effective wetting window can be extended, allowing epoxy resin, modified polyurethane resin, and weather-resistant polyurethane resin to form a continuous coating layer on the fiber surface, avoiding insufficient penetration due to excessively low temperature or residual internal voids due to excessively short time.
[0126] For example, the immersion temperature can be a range of 40°C, 45°C, 50°C, 55°C, 60°C or any combination thereof; the immersion time can be a range of 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or any combination thereof.
[0127] In some specific implementations, the temperature for impregnation treatment in the impregnation zone during the pultrusion process can be 80℃-120℃.
[0128] In some specific implementations, the curing temperature in the curing zone can be 180℃-230℃.
[0129] In some specific implementations, the temperature for heat preservation treatment in the heat preservation zone can be 140℃-180℃.
[0130] In some specific implementations, the pultrusion speed can be 1.2 m / min to 1.6 m / min.
[0131] The three types of impregnated fibers are then introduced into the impregnation treatment section, with the impregnation temperature controlled between 80℃ and 120℃ to promote further resin diffusion, eliminate entrained air bubbles, stabilize the interface wetting state, and enhance the interlayer bonding between the matrix layer, intermediate layer, and protective layer. Following this, a curing treatment is performed at 180℃-230℃, combined with a heat preservation treatment at 140℃-180℃ to ensure full cross-linking of the curing agent and epoxy resin in the system. Simultaneously, the modified polyurethane resin and weather-resistant polyurethane resin complete structural stabilization, forming a composite layered structure with a continuous phase and stable interface. During the impregnation, curing, and heat preservation treatments, pultrusion is carried out at a speed of 1.2m / min-1.6m / min, ensuring that the impregnation, wetting, curing, and heat preservation processes are completed synchronously under continuous traction. This balances molding efficiency with resin flow, venting, and sizing quality, avoiding incomplete impregnation due to excessive speed or reduced production cycle time due to excessively slow speed.
[0132] For example, the temperature of the immersion treatment can be a range of 80°C, 90°C, 100°C, 110°C, 120°C, or any combination thereof.
[0133] For example, the curing temperature can be a range of 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, or any combination thereof.
[0134] For example, the temperature of the insulation treatment can be a range of 140°C, 150°C, 160°C, 170°C, 180°C, or any combination thereof.
[0135] For example, the pultrusion speed can be a range of 1.2 m / min, 1.3 m / min, 1.4 m / min, 1.5 m / min, 1.6 m / min, or any combination thereof.
[0136] In the curing stage, the epoxy resin in the matrix layer forms a high-crosslink density network under the action of the curing agent, and forms a stable interface with the surface of the glass fiber roving through silane coupling, thus forming a high-strength main load-bearing skeleton. The modified polyurethane resin in the intermediate layer forms a polymer phase with both toughness and resistance to damp heat after crosslinking. Together with the biaxial glass fiber stitched fabric, it establishes a longitudinal and transverse stress dispersion system, so that the composite stress generated by wind load, snow load, installation clamping and thermal deformation can be redistributed in the intermediate layer. The weather-resistant polyurethane resin and basalt fiber felt in the protective layer, through dense surface coverage and the stabilizing effect of weather-resistant additives, construct the first barrier against ultraviolet rays, salt spray, damp heat and oxidation environment.
[0137] In this embodiment, by synergistically controlling the impregnation temperature, impregnation time, wetting temperature, curing temperature, holding temperature, and pultrusion speed, the resin system undergoes a continuous transformation within the fiber reinforcement, from low-viscosity penetration, interfacial degassing, cross-linking curing, to overall shaping, thereby forming a matrix layer, intermediate layer, and protective layer adapted to the photovoltaic module frame. The temperature and time range during the impregnation stage balances resin flowability and fiber retention, ensuring that the glass fiber roving, glass fiber woven fabric, and basalt fiber mat are fully impregnated. The impregnation treatment, curing, and holding processes promote complete resin reaction through progressive heat input, reducing porosity and improving interlayer bonding strength. Combined with the limited pultrusion speed, the composite material maintains dimensional stability and cross-sectional consistency during continuous molding, avoiding local resin enrichment or fiber misalignment. This results in a photovoltaic module frame that combines structural strength, weather resistance, and long-term service reliability, making it particularly suitable for long-term outdoor applications in environments with high salt spray, strong ultraviolet radiation, and large temperature differences.
[0138] The preparation method provided in this application achieves a functional gradient transition from the inside out, with the inner layer primarily load-bearing, the middle layer primarily reinforcing and buffering, and the outer layer primarily protecting and stabilizing. Through this layering principle, different material systems no longer bear all service requirements with a single property, but rather form a synergistic performance in the thickness direction of the frame, enabling high stiffness, high toughness, and high weather resistance to be simultaneously achieved in the same profile. Furthermore, the combination of epoxy resin and untwisted glass fiber roving is more suitable for constructing a continuous longitudinal force flow path; the combination of glass fiber stitched fabric and modified polyurethane resin is more suitable for absorbing transverse and interlaminar stresses; and the combination of basalt fiber felt and weather-resistant polyurethane resin is more suitable for improving surface stability and environmental shielding capabilities. Therefore, during long-term thermal cycling, stress concentration caused by differences in material modulus and thermal strain within the frame can be reduced. In coastal and humid environments, the intrusion of corrosive media and moisture can be slowed; and in plateau and desert regions, the degradation rate of the surface layer by ultraviolet radiation and windblown sand can be reduced, thereby ensuring the dimensional stability and structural integrity of the frame under long-term service conditions.
[0139] The method for preparing photovoltaic module frame material provided in this application involves using different fibers corresponding to different resin slurries and employing simultaneous and continuous impregnation, curing, heat preservation, and pultrusion processes. This allows the matrix layer to provide basic support and dimensional stability, the intermediate layer to provide directional reinforcement and bending resistance, and the protective layer to impart weather resistance, UV resistance, and damp heat resistance to the outer surface. The optimal range of each component can control the system viscosity, curing rate, and interlayer bonding strength while ensuring sufficient resin impregnation of the fibers. This reduces molding defects and improves the overall consistency and long-term service reliability of the frame, thereby obtaining a photovoltaic module frame suitable for complex outdoor environments.
[0140] This application also provides a photovoltaic module frame, including the aforementioned photovoltaic module frame material.
[0141] In one possible implementation, the photovoltaic module frame material can be processed into a photovoltaic module frame through post-processing. Post-processing may include cutting, trimming, end chamfering, surface cleaning, and necessary dimensional inspections to ensure the finished frame meets the photovoltaic module assembly requirements, facilitating the splicing of the four sides of the frame and its assembly with module laminates, sealants, and mounting blocks. It should be understood that the above examples are merely illustrative and not limiting.
[0142] The photovoltaic module frame provided in this embodiment can execute the method provided in the above method embodiment. Its implementation principle and technical effect are similar, and will not be described in detail here.
[0143] This application also provides a photovoltaic module, including the aforementioned photovoltaic module frame.
[0144] This photovoltaic module employs a frame surrounding a laminated component. The base layer within the frame provides fundamental support, the intermediate layer enhances load-bearing capacity under lateral and complex loads, and the protective layer forms an external barrier against salt spray, humidity, ultraviolet radiation, and sandstorms. This ensures the module maintains high overall rigidity and edge stability during transportation, hoisting, installation, and long-term outdoor operation. Because the frame combines strength, weather resistance, and dimensional stability, it better adapts to wind pressure, snow load, temperature cycling, and corrosive conditions, reducing the risk of edge stress concentration, cracking, delamination, and seal failure. This, in turn, improves the long-term reliability and service life of the module in large-scale ground-mounted power plants, coastal areas, plateaus, and deserts.
[0145] The technical solution of this application will be further described below using specific embodiments.
[0146] Example 1
[0147] A photovoltaic module frame material, by weight percentage, comprises a substrate layer of 50%, an intermediate layer of 35%, and a protective layer of 15%.
[0148] The matrix layer, by weight percentage, comprises 35% bisphenol F type epoxy resin, 60% 2400 tex alkali-free untwisted glass fiber roving, 1.5% silane coupling agent (epoxy silane coupling agent (KH-560)), 3% rubber toughening agent (carboxyl-terminated nitrile butadiene rubber (CTBN)), and 2% amino curing agent (isophorone diamine (IPDA)); the intermediate layer comprises a surface density of 450 g / m³. 2 The material consists of 70% biaxial fiberglass stitched fabric and 30% modified polyurethane resin; the protective layer comprises a surface density of 60 g / m². 2 The composition consists of 50% basalt fiber felt, 47% hexamethylene diisocyanate modified polyurethane resin, 1% ultraviolet absorber (UV-1577), 1% light stabilizer (HALS-944), and 1% antioxidants (antioxidant 1010 and antioxidant 168).
[0149] The preparation method steps are as follows:
[0150] 2400tex alkali-free, untwisted glass fiber roving with an areal density of 450 g / m² is used. 2 Biaxial glass fiber stitch-woven fabric with an areal density of 60 g / m 2 The basalt fiber felt was dried at 100℃ for 30 minutes to reduce its moisture content to below 0.1%;
[0151] The resin slurry for the matrix layer, intermediate layer, and protective layer is prepared according to the following mass percentages: 35% bisphenol F epoxy resin, 60% 2400tex alkali-free untwisted glass fiber roving, 1.5% silane coupling agent, 3% rubber toughening agent, and 2% amino curing agent; 70% biaxial glass fiber stitched fabric and 30% polyether-modified polyurethane resin; and 50% basalt fiber felt, 47% hexamethylene diisocyanate modified polyurethane resin, 1% ultraviolet absorber, 1% light stabilizer, and 1% antioxidant.
[0152] The following materials were impregnated: alkali-free untwisted glass fiber roving and matrix layer resin slurry at a mass-to-volume ratio of 0.45 mL: 1 g; biaxial glass fiber stitched fabric and intermediate layer resin slurry at a mass-to-volume ratio of 0.35 mL: 1 g; and basalt fiber felt and protective layer resin slurry at a mass-to-volume ratio of 0.50 mL: 1 g. The impregnation temperature was controlled at 50°C and the impregnation time was 12 min.
[0153] The three types of impregnated fibers were subjected to impregnation, curing, and heat preservation treatments in sequence at a pultrusion speed of 1.4 m / min. The impregnation temperature was 100℃, the curing temperature was 210℃, and the heat preservation temperature was 160℃. The final photovoltaic module frame material was obtained.
[0154] Example 2
[0155] A photovoltaic module frame material, by weight percentage, comprises a substrate layer of 55%, an intermediate layer of 30%, and a protective layer of 15%.
[0156] The matrix layer, by weight percentage, comprises 38% bisphenol F type epoxy resin, 57% 1200 tex alkali-free untwisted glass fiber roving, 1% silane coupling agent (epoxy silane coupling agent (KH-560)), 3% rubber toughening agent (carboxyl-terminated nitrile butadiene rubber (CTBN)), and 1% amino curing agent (isophorone diamine (IPDA)); the intermediate layer comprises a surface density of 500 g / m³. 2 The composition is 65% biaxial fiberglass stitched fabric and 35% modified polyurethane resin (polyether-modified polyurethane); the protective layer includes a surface density of 80 g / m². 2 The composition is 48% basalt fiber felt, 49% hexamethylene diisocyanate modified polyurethane resin, 1.2% ultraviolet absorber (UV-1577), 0.8% light stabilizer (antioxidant 1010) and 1% antioxidant (antioxidant 1010 and antioxidant 168).
[0157] The preparation method is basically the same as in Example 1, except that the formulation of each resin slurry is adjusted according to the mass fraction of each component; the impregnation temperature is 55°C, the impregnation time is 10 min, the wetting treatment temperature is 110°C, the curing treatment temperature is 220°C, the heat preservation treatment temperature is 170°C, and the pultrusion speed is 1.2 m / min.
[0158] Example 3
[0159] A photovoltaic module frame material, the structure of which is basically the same as that of Example 1.
[0160] The preparation method is basically the same as that in Example 1, except that the impregnation temperature is 60°C, the impregnation time is 15 min, the wetting temperature is 120°C, the curing temperature is 230°C, the heat preservation temperature is 180°C, and the pultrusion speed is 1.6 m / min.
[0161] Example 4
[0162] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, differs in that the linear density of the alkali-free, untwisted coarse glass fiber sand used is 4800 tex, and the areal density of the biaxial glass fiber stitched fabric is 650 g / m². 2 The areal density of basalt fiber felt is 100 g / m³. 2 .
[0163] Its preparation method is basically the same as that in Example 1.
[0164] Example 5
[0165] A photovoltaic module frame material, whose structure is basically the same as that of Example 2, except that the areal density of the biaxial glass fiber stitched fabric is 300 g / m². 2 The areal density of basalt fiber felt is 30 g / m³. 2 .
[0166] Its preparation method is basically the same as that in Example 1.
[0167] Example 6
[0168] A photovoltaic module frame material, whose structure is basically the same as that of Example 4, differs in that the linear density of the alkali-free, untwisted coarse glass fiber sand used is 5000 tex, and the areal density of the biaxial glass fiber stitched fabric is 700 g / m². 2 The areal density of basalt fiber felt is 110 g / m³. 2 .
[0169] Its preparation method is basically the same as that in Example 1.
[0170] Example 7
[0171] A photovoltaic module frame material, whose structure is basically the same as that of Example 5, differs in that the linear density of the alkali-free, untwisted coarse glass fiber sand used is 1000 tex, and the areal density of the biaxial glass fiber stitched fabric is 250 g / m². 2 The areal density of basalt fiber felt is 20 g / m³. 2 .
[0172] Its preparation method is basically the same as that in Example 1.
[0173] Example 8
[0174] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, differs in that, by mass percentage, the matrix layer comprises 30% bisphenol F type epoxy resin, 65% 2400tex alkali-free untwisted glass fiber roving, 1% silane coupling agent (epoxy silane coupling agent (KH-560)), 2% rubber toughening agent (carboxyl-terminated nitrile butadiene rubber (CTBN)), and 2% amino curing agent (isophorone diamine (IPDA)); the intermediate layer comprises a surface density of 450 g / m². 2 It consists of 60% biaxial glass fiber stitched fabric and 40% modified polyurethane resin.
[0175] Its preparation method is basically the same as that in Example 1.
[0176] Example 9
[0177] A photovoltaic module frame material, whose structure is basically the same as that of Example 8, differs in that, by mass percentage, the matrix layer contains 28% bisphenol F epoxy resin and 67% 2400tex alkali-free untwisted glass fiber roving; the intermediate layer has an areal density of 450 g / m³. 2 The biaxial glass fiber stitched fabric has a mass fraction of 55% and modified polyurethane resin of 45%.
[0178] Its preparation method is basically the same as that in Example 1.
[0179] Example 10
[0180] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, differs in that, by mass percentage, the matrix layer comprises 40% bisphenol F type epoxy resin, 50% 2400tex alkali-free untwisted glass fiber roving, 2% silane coupling agent (epoxy silane coupling agent (KH-560)), 5% rubber toughening agent (carboxyl-terminated nitrile butadiene rubber (CTBN)), and 3% amino curing agent (isophorone diamine (IPDA)); the intermediate layer comprises a surface density of 450 g / m². 2 It consists of 75% biaxial glass fiber stitched fabric and 25% modified polyurethane resin.
[0181] Its preparation method is basically the same as that in Example 1.
[0182] Example 11
[0183] A photovoltaic module frame material, whose structure is basically the same as that of Example 10, differs in that, by mass percentage, the matrix layer contains 42% bisphenol F epoxy resin and 48% 2400tex alkali-free untwisted glass fiber roving; the intermediate layer has an areal density of 450 g / m³. 2 The biaxial glass fiber stitch-woven fabric has a mass fraction of 80% and modified polyurethane resin of 20%.
[0184] Its preparation method is basically the same as that in Example 1.
[0185] Comparative Example 1
[0186] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, except that the matrix layer does not include untwisted glass fiber sand.
[0187] The preparation method is basically the same as that in Example 1, except that glass fiber untwisted coarse sand is not added when preparing the matrix layer resin slurry.
[0188] Comparative Example 2
[0189] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, except that the intermediate layer does not include biaxial glass fiber stitched fabric.
[0190] The preparation method is basically the same as that in Example 1, except that biaxial glass fiber stitched fabric is not added when preparing the intermediate layer resin slurry.
[0191] Comparative Example 3
[0192] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, except that the protective layer does not include basalt fiber felt.
[0193] Its preparation method is basically the same as that in Example 1, except that basalt fiber felt is not added when preparing the protective layer resin slurry.
[0194] Comparative Example 4
[0195] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, except that it does not include an intermediate layer and a protective layer.
[0196] The preparation method is basically the same as that in Example 1, except that only the substrate layer is prepared, and the intermediate layer and protective layer are not prepared.
[0197] Comparative Example 5
[0198] A photovoltaic module frame material, whose structure is basically the same as that of Example 1, except that it does not include a protective layer.
[0199] The preparation method is basically the same as that in Example 1, except that only the substrate layer and intermediate layer are prepared, and the protective layer is not prepared.
[0200] Comparative Example 6
[0201] The commercially available 6063-T5 photovoltaic aluminum alloy frame material was purchased from Yongzhen Technology Co., Ltd.
[0202] The following performance tests were performed on the materials prepared in the above embodiments and comparative examples:
[0203] Tensile strength: Tested according to GB / T 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics";
[0204] Flexural strength: Tested according to GB / T 1449-2005 "Test Method for Flexural Properties of Fiber Reinforced Plastics";
[0205] Density: Tested according to GB / T 1463-2005 "Test Methods for Density and Relative Density of Fiber Reinforced Plastics";
[0206] Salt spray resistance test: The test was conducted in accordance with GB / T 18912-2024 "Salt spray corrosion test for photovoltaic modules";
[0207] Thermal expansion coefficient test: The test was conducted in accordance with GB / T 2572-2006 "Test method for average linear expansion coefficient of fiber reinforced plastics".
[0208] The test results are detailed in Table 1.
[0209] Table 1
[0210]
[0211] As shown in Table 1, the photovoltaic module frame material provided in this application has excellent mechanical strength and corrosion resistance, and its density is low, which can meet the requirements of lightweight applications. At the same time, its coefficient of thermal expansion is also low, which can ensure structural stability under temperature difference cycling conditions.
[0212] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and various modifications and changes may be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A photovoltaic module frame material, characterized in that, Includes a base layer, an intermediate layer, and a protective layer; The matrix layer comprises epoxy resin and glass fiber roving; The intermediate layer comprises a glass fiber woven fabric and a modified polyurethane resin; The protective layer comprises basalt fiber felt and weather-resistant polyurethane resin.
2. The photovoltaic module frame material according to claim 1, characterized in that, The linear density of the glass fiber roving is 1200 tex-4800 tex; And / or, the epoxy resin includes bisphenol F type epoxy resin; And / or, the areal density of the glass fiber stitch-woven fabric is 300 g / m². 2 -650g / m 2 ; And / or, the modified polyurethane resin includes at least one of polyether-modified polyurethane, polyester-modified polyurethane, epoxy-modified polyurethane, amino-terminated polyether-modified polyurethane, and silicone-modified polyurethane. And / or, the areal density of the basalt fiber felt is 30 g / m³. 2 -100g / m 2 ; And / or, the weather-resistant polyurethane resin includes aliphatic isocyanate-modified polyurethane.
3. The photovoltaic module frame material according to claim 2, characterized in that, The glass fiber stitched fabric includes a biaxial glass fiber stitched fabric; And / or, the aliphatic isocyanate modified polyurethane includes at least one of hexamethylene diisocyanate modified polyurethane, isophorone diisocyanate modified polyurethane, dicyclohexylmethane diisocyanate modified polyurethane, and tetramethylxylene diisocyanate modified polyurethane.
4. The photovoltaic module frame material according to any one of claims 1-3, characterized in that, By weight percentage, the matrix layer comprises: 30%-40% epoxy resin, 50%-65% glass fiber roving, 1%-2% silane coupling agent, 2%-5% toughening agent, and 1%-3% curing agent; And / or, the intermediate layer comprises: 60%-75% of the glass fiber stitched fabric and 25%-40% of the modified polyurethane resin; And / or, the protective layer comprises: 45%-55% of the basalt fiber felt, 40%-50% of the weather-resistant polyurethane resin, 0.5%-1.5% of the ultraviolet absorber, 0.3%-1% of the light stabilizer, and 0.2%-0.8% of the antioxidant.
5. The photovoltaic module frame material according to claim 4, characterized in that, The silane coupling agent includes at least one of aminosilane coupling agents, epoxysilane coupling agents, and mercaptosilane coupling agents; And / or, the toughening agent includes at least one of liquid nitrile rubber, carboxyl-terminated nitrile rubber, core-shell acrylate, and polyether polyurethane; And / or, the curing agent includes at least one of aliphatic polyamines, aromatic amines, cycloaliphatic amines, and phenolic amines; And / or, the ultraviolet absorber includes at least one of benzotriazole ultraviolet absorbers, triazine ultraviolet absorbers, and benzophenone ultraviolet absorbers; And / or, the light stabilizer includes hindered amine compounds; And / or, the antioxidant includes at least one of phenolic antioxidants, phosphite antioxidants, and thioether antioxidants.
6. The photovoltaic module frame material according to any one of claims 1-5, characterized in that, By weight percentage, the photovoltaic module frame material comprises 40%-55% of the substrate layer, 30%-40% of the intermediate layer, and 10%-15% of the protective layer.
7. A method for preparing a photovoltaic module frame material according to any one of claims 1-6, characterized in that, include: The matrix layer resin slurry, intermediate layer resin slurry, and protective layer resin slurry are prepared separately, and then the glass fiber roving, the glass fiber stitched fabric, and the basalt fiber felt are impregnated into the corresponding matrix layer resin slurry, intermediate layer resin slurry, and protective layer resin slurry. The three types of impregnated fibers are simultaneously subjected to impregnation, curing and heat preservation treatments in sequence under pultrusion to obtain the photovoltaic module frame material.
8. The preparation method according to claim 7, characterized in that, The matrix resin slurry includes a silane coupling agent, a toughening agent, a curing agent, and the epoxy resin; And / or, the intermediate layer resin slurry includes the modified polyurethane resin; And / or, the protective layer resin slurry includes an ultraviolet absorber, a light stabilizer, an antioxidant, and the weather-resistant polyurethane resin.
9. The preparation method according to claim 7 or 8, characterized in that, The volume-to-mass ratio of the matrix resin slurry to the glass fiber roving is (0.35-0.55) mL: 1 g; And / or, the volume-to-mass ratio of the intermediate layer resin slurry to the glass fiber stitched fabric is (0.28-0.42) mL: 1 g; And / or, the volume-to-mass ratio of the protective layer resin slurry to the basalt fiber felt is (0.40-0.60) mL:1g.
10. The preparation method according to any one of claims 7-9, characterized in that, The immersion temperature is 40℃-60℃, and the immersion time is 10min-15min; And / or, the temperature of the immersion treatment is 80℃-120℃; And / or, the curing temperature is 180℃-230℃; And / or, the temperature of the heat preservation treatment is 140℃-180℃; And / or, the pultrusion speed is 1.2 m / min to 1.6 m / min.
11. A photovoltaic module frame, characterized in that, The photovoltaic module frame material includes the photovoltaic module frame material according to any one of claims 1-6 or the photovoltaic module frame material prepared by the preparation method according to any one of claims 7-10.
12. A photovoltaic module, characterized in that, Includes the photovoltaic module frame as described in claim 11.